A work group report on ultrafine particles (American Academy of Allergy, Asthma & Immunology): Why ambient ultrafine and engineered nanoparticles should receive special attention for possible adverse health outcomes in human subjects - Li, Ning; Georas, Steve; Alexis, Neil; Fritz, Patricia; Xia, Tian; Williams, Marc A.; Horner, Elliott; Nel, Andre (Journal of allergy and clinical immunology, 2016)
Ultrafine particles (UFPs) are airborne particulates of less than 100 nm in aerodynamic diameter. Examples of UFPs are diesel exhaust particles, products of cooking, heating, and wood burning in indoor environments, and, more recently, products generated through the use of nanotechnology. Studies have shown that ambient UFPs have detrimental effects on both the cardiovascular and respiratory systems, including a higher incidence of atherosclerosis and exacerbation rate of asthma. UFPs have been found to alter in vitro and in vivo responses of the immune system to allergens and can also play a role in allergen sensitization. The inflammatory properties of UFPs can be mediated by a number of different mechanisms, including the ability to produce reactive oxygen species, leading to the generation of proinflammatory cytokines and airway inflammation. In addition, because of their small size, UFPs also have unique distribution characteristics in the respiratory tree and circulation and might be able to alter cellular function in ways that circumvent normal signaling pathways. Additionally, UFPs can penetrate intracellularly and potentially cause DNA damage. The recent advances in nanotechnology, although opening up new opportunities for the advancement of technology and medicine, could also lead to unforeseen adverse health effects in exposed human subjects. Further research is needed to clarify the safety of nanoscale particles, as well as the elucidation of the possible beneficial use of these particulates to treat disease. [Display omitted]